EFEKTIVITAS PROGRAM BERAS MISKIN (RASKIN) DI KELURAHAN KUALA LAHANG KECAMATAN GAUNG KABUPATEN INDRAGIRI HILIR - jurnalmap map; Azwarni ÔÇÄ; Hadi Susanto; Esa Wahyu Endarti (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
The Raskin program is actually part of the government's efforts to overcome the problem of poverty. The location of this research is in the Village of Kuala Lahang, Gaung Subdistrict, Indragiri Hilir Regency with the aim of describing the process of implementing a program of rice assistance for poor families, to describe the effectiveness of the rice assistance program for poor families and to describe the supporting factors and obstacles to the implementation of the family rice assistance program poor. Data sources were obtained that relate to the RASKIN distribution and distribution process, mainly sourced from beneficiary households (RTS) beneficiaries and RASKIN management teams at the village and sub-district levels using the method of observation, interview and documentation. The results of the study revealed that the implementation of the rice assistance program for poor families in Gaung District had not been carried out effectively in accordance with the applicable provisions and procedures.